A we43 magnesium alloy material and a method of making the same

CN122879575APending Publication Date: 2026-10-09NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611376060.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]在WE43镁合金中,常用锆元素作为细化剂,锆元素简写为Zr,并且Zr的熔点高,具体为1855℃,需以Mg-Zr中间合金形式加入,易因密度差异导致熔体中分布不均

Benefits of technology

(1)本发明通过选择Gd作为合金化元素,起到显著的第二相强化以及晶粒细化效果,并通过Al与合金元素充分反应,Al作为变质剂细化合金晶粒,以改善合金的组织,提升其强度和塑性。本发明提供的WE43镁合金材料中Y的质量分数为3.6~4.4%,Nd的质量分数2.7~3.3%,Gd的质量分数1.8~2.2%以及Al的质量分数1.5~2.0%,能很好的兼顾抗拉强度与延伸率,能同时满足极限拉伸强度在219MPa以上、拉伸屈服强度在309MPa以上以及延伸率在10.6%以上;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879575A_ABST
    Figure CN122879575A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of alloy materials, and particularly relates to a WE43 magnesium alloy material and a preparation method thereof, which at least comprises the following components in percentage by mass: Y: 3.6-4.4%, Nd: 2.7-3.3%, Gd: 1.8-2.2%, and Al: 1.5-2.0%, and the balance is Mg. By selecting Gd as an alloying element, a significant second phase strengthening and grain refinement effect are achieved, and by selecting Al as a modifier, the alloy grains are refined, so that the structure of the alloy is improved, and the strength and plasticity of the alloy are improved. The WE43 magnesium alloy material provided by the application can well balance the tensile strength and elongation, and can simultaneously satisfy the conditions that the ultimate tensile strength is above 219 MPa, the tensile yield strength is above 309 MPa, and the elongation is above 10.6%. Meanwhile, in the preparation method, the electric pulse treatment can effectively improve the comprehensive performance of the rare earth magnesium alloy, can make the alloy precipitate subcrystals, can increase the dislocation density, can promote the dissolution, spheroidization and uniform distribution of the second phase or precipitated phase, and can significantly improve the elongation of the alloy, and the treatment time is as low as milliseconds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alloy materials technology, specifically relating to a WE43 magnesium alloy material and its preparation method. Background Technology

[0002] Traditional magnesium-yttrium-neodymium (Mg-Y-Nb) alloys are widely used in complex thin-walled structural components in the aerospace field due to their excellent strengthening effect and superior room-temperature comprehensive mechanical properties. Most magnesium alloys, especially cast Mg-RE alloys, have a high Hall-Petch coefficient, so grain refinement can significantly improve their mechanical properties and is one of the most important strengthening methods. Therefore, by optimizing alloy composition design and improving the preparation process, grain refinement and precipitate distribution can be further improved, thereby enhancing the overall performance of the alloy.

[0003] In WE43 magnesium alloys, zirconium (Zr) is commonly used as a refining agent. Zr has a high melting point of 1855℃ and must be added as a Mg-Zr master alloy. However, its uneven distribution in the melt is easily caused by density differences. Furthermore, Zr has extremely low solubility in magnesium alloy melts, easily precipitating and oxidizing, leading to the loss of Zr and other rare earth elements, resulting in inaccurate alloy composition in casting. Therefore, the Mg-Zr master alloy must be added as the final step in the smelting process, and casting must be completed within 30 minutes of Zr addition. Prolonged storage increases the requirements for process design and smelting equipment. Additionally, the high price of Mg-Zr master alloys makes mass production too costly. Currently, developing an alloy system with comprehensive performance suitable for the aerospace field while reducing production costs is a pressing issue in the WE43 magnesium alloy material industry. Summary of the Invention

[0004] This invention addresses the shortcomings of existing technologies by proposing a WE43 magnesium alloy material and its preparation method. By replacing Zr with Al, Al reacts fully with the alloying elements, acting as a modifier to refine the alloy grains, effectively improving the alloy's microstructure and enhancing its strength and plasticity. Simultaneously, the preparation method utilizes solid solution treatment combined with electro-pulse treatment to develop a simpler and lower-cost economical high-strength rare-earth magnesium alloy, providing a new solution for high-performance magnesium alloy applications in aerospace and other fields.

[0005] The price of pure Al is only a fraction of that of Zr of the same mass, and Al has a high solid solubility in the magnesium matrix, approximately 12.7 wt%. Zr's grain-refining effect in WE43 stems from Zr particles acting as a heterogeneous nucleation substrate for α-Mg. However, Zr's density of 7.8 g / cm³ is much higher than Mg's density of 1.7 g / cm³, making it prone to sedimentation during smelting, leading to Zr loss and low utilization. When Al replaces Zr, Al does not directly act as a grain refiner; instead, it reacts with rare earth elements such as Y, Nd, or Gd to form thermodynamically stable Al₂RE-type Laves phases, such as Al₂Y, Al₂Nd, and Al₂Gd. These Laves phases are simply referred to as Laves phases. These Al2RE phase particles exhibit a clear crystal orientation relationship with the α-Mg matrix ({0001}α-Mg / / {111}Al2RE, {10-10}α-Mg / / {101}Al2RE, {11-20}α-Mg / / {112}Al2RE), serving as effective heterogeneous nucleation sites. More importantly, the Al2RE phase exhibits significantly better thermal stability than Zr particles, effectively suppressing grain coarsening during high-temperature heat treatment, resulting in excellent thermal stability and a wider heat treatment process window for the alloy. During casting, Al has a low melting point (660℃), allowing for direct addition of pure Al with a much lower Al burn-off rate than Zr, enabling more precise composition control. Furthermore, there are no strict casting time requirements after Al addition, facilitating process design and optimization for practical applications.

[0006] The first objective of this invention is to provide a WE43 magnesium alloy material comprising, by mass percentage, at least the following components: Y: 3.6%~4.4%, Nd: 2.7%~3.3%, Gd: 1.8%~2.2% and Al: 1.5%~2.0%, with the balance being Mg.

[0007] The second objective of this invention is to provide a method for preparing the above-mentioned WE43 magnesium alloy material, comprising the following steps: The pretreated raw materials were melted to obtain magnesium alloy melt; Magnesium alloy melt is cast to obtain magnesium alloy ingots; Magnesium alloy ingots were subjected to solution heat treatment to obtain magnesium alloy ingots in the T4 state. The WE43 magnesium alloy material was obtained by subjecting a T4 state magnesium alloy ingot to electrical pulse treatment. The raw materials include pure Mg, Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, Mg-30wt.%Gd master alloy, and pure Al.

[0008] Furthermore, considering the burn-off rate, the mass percentages of each raw material are as follows: Mg-30wt.%Y master alloy 15.0%~18.3%, Mg-30wt.%Nd master alloy 11.3~14.3%, Mg-30wt.%Gd master alloy 7.5~9.2%, and Al 1.5~2.0%, with the balance being pure Mg.

[0009] Furthermore, the pretreatment method includes drying the raw material and preheating it to 180°C~200°C.

[0010] Furthermore, the melting step includes: Pure Mg is heated to 720℃~750℃ to melt and held at that temperature to obtain the first melt; Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, and Mg-30wt.%Gd master alloy were added to the first melt, mixed evenly, and kept at a certain temperature to obtain the second melt. After heating the second melt to 750℃~780℃, add pure Al, mix evenly and keep warm to obtain the third melt; After cooling the third melt to 690℃~710℃, a magnesium alloy melt is obtained.

[0011] During the melting process, slag removal is required each time new metal is added to remove oxides from the first and second melts, ensuring melt purity and preventing secondary contamination.

[0012] Furthermore, both the melting and casting are carried out in a protective gas, which is a mixture of CO2 and SF6 in a volume ratio of 99:1.

[0013] Furthermore, the casting process also includes the step of immersing the solidified magnesium alloy melt in water for cooling.

[0014] Furthermore, the solution heat treatment includes coating the Mg alloy ingot with carbon powder and holding it at a temperature of 510℃~530℃ at a heating rate of 5℃ / min for 4h~8h. If the temperature rises too quickly, the temperature difference between the ingot surface and the core will create excessive thermal stress, which will damage the alloy properties.

[0015] Furthermore, the solution heat treatment further includes a cooling step, wherein the cooling temperature is 90℃~100℃. Rapid cooling effectively suppresses grain coarsening, thereby significantly refining the grains.

[0016] Furthermore, before the electrical pulse treatment, the T4-state Mg alloy ingot is machined into a long strip shape, and its surface is polished. Machined into a long strip shape and polished, the oxide scale on the surface of the T4-state Mg alloy ingot is effectively removed, while ensuring good conductivity.

[0017] Furthermore, the current density of the electrical pulse processing is 100 A / mm. 2 ~125A / mm 2 The energizing time is 520ms~600ms. For Mg alloys, 100A / mm²~125A / mm² falls within the medium-high current density range. This density is sufficient to generate a significant electron wind effect. Too low a current or too short an energizing time may lead to insufficient energy input and incomplete recrystallization; too high a current or too long an energizing time may cause heat accumulation and increase the risk of grain coarsening.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention selects Gd as an alloying element, which has a significant effect on second-phase strengthening and grain refinement. Al reacts fully with the alloying elements, and Al acts as a modifier to refine the alloy grains, thereby improving the microstructure of the alloy and enhancing its strength and plasticity. The WE43 magnesium alloy material provided by this invention has a mass fraction of Y of 3.6~4.4%, a mass fraction of Nd of 2.7~3.3%, a mass fraction of Gd of 1.8~2.2%, and a mass fraction of Al of 1.5~2.0%, which can well balance tensile strength and elongation, and can simultaneously meet the requirements of ultimate tensile strength above 219MPa, tensile yield strength above 309MPa, and elongation above 10.6%.

[0019] (2) After obtaining the magnesium alloy ingot, the present invention utilizes electrical pulse treatment to effectively improve the comprehensive performance of rare earth magnesium alloys. The high-density electron flow can induce a violent Joule heating effect in a very short time, and this instantaneous high temperature can provide a driving force for recrystallization. At the same time, electrical pulse treatment not only causes the alloy to precipitate subgrains and increase the dislocation density, but also promotes the dissolution, spheroidization and uniform distribution of the second phase or precipitated phase. Compared with traditional aging heat treatment, electrical pulse treatment can significantly improve the elongation of the alloy and reduce the treatment time from tens of hours to hundreds of milliseconds. Attached Figure Description

[0020] Figure 1 This is a metallographic structure diagram of the WE43 magnesium alloy prepared in Example 1 of the present invention; Figure 2 The image shows the metallographic structure of the WE43 magnesium alloy prepared in Example 2 of this invention, observed under a 200x microscope. Figure 3 For the present invention Figure 2 A magnified view of a portion of the image; Figure 4 This is a scanning electron microscope image (SEM image) of the WE43 magnesium alloy prepared in Example 2 of the present invention. Figure 5The metallographic structure diagram of the WE43 magnesium alloy prepared in Comparative Example 1 of this invention is shown. Figure 6 The metallographic structure diagram of the WE43 magnesium alloy prepared in Comparative Example 3 of this invention is shown. Figure 7 This is a scanning electron microscope image (SEM image) of the WE43 magnesium alloy prepared in Comparative Example 3 of the present invention. Figure 8 The diagram shows the pulse current processing device of the present invention, wherein 1 is a voltage regulator; 2 is a time control switch; 3 is a transformer; 4 is a copper electrode; and 5 is a sample. Figure 9 This is a structural diagram of the test specimen for the WH-5000 microcomputer-controlled electronic universal testing machine of the present invention. The dimensions are in mm. Detailed Implementation

[0021] Hereinafter, embodiments of the present invention will be described in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0022] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. The range defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range.

[0023] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0024] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0025] Unless otherwise specified, the term "comprising" as used in this application can be either open-ended or closed-ended. For example, "comprising" may mean that it may also include other components not listed, or it may only include the listed components.

[0026] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true and B is false; A is false and B is true; or both A and B are true.

[0027] Unless otherwise specified, in this application, the terms "first," "second," "third," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.

[0028] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0029] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application.

[0030] The equipment used in this invention is shown in the table below: This invention discloses a method for preparing WE43 magnesium alloy material, including the following specific steps: Step 1: Preprocessing Cut pure Mg, Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, Mg-30wt.%Gd master alloy, and pure Al according to the designed alloy composition. When cutting the specific alloys, consider a 20% loss of Mg, 25% loss of Y, and 20% loss of Nd. Calculate the mass percentage of each raw material as follows: Mg-30wt.%Y master alloy 15%~18.3%, Mg-30wt.%Nd master alloy 11.3~14.3%, Mg-30wt.%Gd master alloy 7.5~9.2%, and Al 1.5~2.0%, with the balance being pure Mg. Use a grinder to remove the oxide scale and dirt from the surface. Place all materials in a 180℃ electric heating forced-air drying oven for later use.

[0031] After cleaning the stainless steel crucible, alumina crucible, stirring rod, and slag skimmer, prepare the refractory coating with a composition of talc:water:water glass = 3:2.5:2. Dry the crucible, stirring rod, and slag skimmer, apply the coating, and then bake them in a 180℃ drying oven for 20 minutes.

[0032] In actual operation, in order to ensure the purity of each melt after subsequent melting, the stainless steel crucible, alumina crucible, stirring rod and slag ladle need to be taken out to observe the coating, and then coated again to fill in any areas that were not coated evenly. They are then placed in a drying oven to dry for later use. This effectively prevents the crucible, stirring rod and slag ladle from directly contacting the melted parts, thereby ensuring their purity.

[0033] Step 2: Melting The pit-type resistance furnace was set to a temperature of 720℃, with a protective gas composition of CO2:SF6 = 99:1 and a gas flow rate of 2L / min. A stainless steel crucible was placed in the pit-type resistance furnace and heated. When the stainless steel crucible reached 600℃, pure Mg was added to the stainless steel crucible, and protective gas was simultaneously introduced into the furnace to prevent metal oxidation. After the protective gas temperature rose to 720℃, the furnace was opened and slag was skimmed off. Then, Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, and Mg-30wt.%Gd master alloy were added. After melting, the mixture was stirred for 2-3 minutes and held at that temperature for 10 minutes. The melt temperature was then raised to 750℃-780℃, the furnace was opened and slag was skimmed off, then pure Al was added and stirred for 3-5 minutes. The mixture was then held at that temperature for 20 minutes to allow the pure Al to fully react with the other elements, resulting in a magnesium alloy melt.

[0034] Step 3: Casting Set the pit-type resistance furnace to 720℃, insert a thermocouple into the molten magnesium alloy to accurately measure the temperature, and wait for the molten magnesium alloy to cool to 715℃~725℃. First, remove the slag, then pour the molten magnesium alloy into a pure copper mold held at 200℃. During casting, continuously purge the molten magnesium alloy with a protective gas mixture of CO2:SF6 = 99:1. After the molten magnesium alloy cools naturally, remove the magnesium alloy ingot from the mold.

[0035] Step 4: Solution heat treatment Magnesium alloy ingots are placed in alumina crucibles and then completely covered with carbon powder to prevent contact with oxygen. The alumina crucibles are then placed in a box-type resistance furnace for solution heat treatment at 510℃~530℃, a heating rate of 5℃ / min, and a holding time of 4h~8h. After treatment, the magnesium alloy ingots are removed and rapidly cooled in hot water above 90℃~100℃. Once completely cooled, the ingots are removed and air-dried to obtain T4-state magnesium alloy ingots.

[0036] Step 5: Electrical Pulse Processing The T4-state magnesium alloy ingot was machined into a long strip shape. The surface of the magnesium alloy ingot was polished to remove the oxide scale to ensure good conductivity. Then, the long strip-shaped T4-state magnesium alloy ingot was clamped in a... Figure 8 The pulse current processing device shown has a current density set to 100 A / mm between the two copper electrodes.2 ~125A / mm 2 The energizing time is controlled between 520ms and 600ms to obtain the WE43 magnesium alloy material of this invention.

[0037] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings.

[0038] Example 1 Pretreatment: Following the pretreatment method described above, cut 1000g of pure Mg, 215.5g of Mg-30wt.%Y master alloy, 172.5g of Mg-30wt.%Nd master alloy, 86.3g of Mg-30wt.%Gd master alloy, and 19.5g of pure Al. Use a grinder to remove the oxide scale and dirt from their surfaces. Place all materials in a 180℃ electric heating forced-air drying oven for later use. After cleaning the stainless steel crucible, alumina crucible, stirring rod, and slag ladle, prepare the refractory coating. The coating composition is talc:water:water glass = 3:2.5:2. After drying the crucible, stirring rod, and slag ladle, apply the coating and then bake them in a 180℃ drying oven for 20 minutes.

[0039] Melting: The temperature of the pit-type resistance furnace was set to 720℃, the protective gas composition was CO2:SF6 = 99:1, and the gas flow rate was 2L / min. A stainless steel crucible was placed in the pit-type resistance furnace and heated. When the stainless steel crucible reached 600℃, pure Mg was placed into the stainless steel crucible, and protective gas was simultaneously introduced into the furnace. After the protective gas temperature rose to 720℃, the furnace was opened and slag was skimmed off. Then, Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, and Mg-30wt.%Gd master alloy were added. After melting, the mixture was stirred for 2 minutes and held at that temperature for 10 minutes. The melt temperature was then raised to 750℃, the furnace was opened and slag was skimmed off, then pure Al was added and stirred for 3 minutes. After that, the temperature was held for 20 minutes to allow the pure Al to fully react with the other elements, obtaining a magnesium alloy melt.

[0040] Casting: Set the pit-type resistance furnace to 720℃, insert a thermocouple into the molten magnesium alloy to accurately measure the temperature, and wait for the molten magnesium alloy to cool down to 720℃. First, remove the slag, then pour the molten magnesium alloy into a pure copper mold at 200℃. During casting, continuously purge the molten magnesium alloy with a protective gas of CO2:SF6 = 99:1. After the molten magnesium alloy cools naturally, remove the magnesium alloy ingot from the mold and place it in water to continue cooling. After cooling to room temperature, remove and dry it.

[0041] Solution heat treatment: The magnesium alloy ingot was placed in an alumina crucible, and then the ingot was completely covered with carbon powder to prevent it from contacting oxygen. The alumina crucible was then placed in a box-type resistance furnace for solution heat treatment at 510℃, with a heating rate of 5℃ / min and a holding time of 6 hours. After treatment, the magnesium alloy ingot was removed and rapidly cooled in 90℃ hot water. After complete cooling, it was removed and dried to obtain a T4 state magnesium alloy ingot.

[0042] Pulse current processing: The T4 state magnesium alloy ingot is machined into a long strip shape, the surface of the magnesium alloy ingot is polished, and then the long strip T4 state magnesium alloy ingot is clamped between two copper electrodes of the pulse current processing device, and the current density is set to 125A / mm. 2 The energizing time was controlled at 560ms to obtain the WE43 magnesium alloy material of this invention, with the metallographic structure as follows: Figure 1 As shown, electrical pulse processing is abbreviated as EPT processing.

[0043] The WE43 magnesium alloy material prepared in Example 1 has the following composition by mass percentage: Y: 4.0%, Nd: 3.0%, Gd: 2.0%, Al: 1.5%, with the remainder being Mg.

[0044] Example 2 Pretreatment: Following the pretreatment method described above, cut 1000g of pure Mg, 215.5g of Mg-30wt.%Y master alloy, 172.5g of Mg-30wt.%Nd master alloy, 86.3g of Mg-30wt.%Gd master alloy, and 26g of pure Al. Use a grinder to remove the oxide scale and dirt from their surfaces. Place all materials in a 180℃ electric heating drying oven for later use. After cleaning the stainless steel crucible, alumina crucible, stirring rod, and slag ladle, prepare the refractory coating. The coating composition is talc:water:water glass = 3:2.5:2. After drying the crucible, stirring rod, and slag ladle, apply the coating and then bake them in a 180℃ drying oven for 20 minutes.

[0045] Melting: The temperature of the pit-type resistance furnace was set to 720℃, the protective gas composition was CO2:SF6 = 99:1, and the gas flow rate was 2L / min. A stainless steel crucible was placed in the pit-type resistance furnace and heated. When the stainless steel crucible reached 600℃, pure Mg was placed into the stainless steel crucible, and protective gas was simultaneously introduced into the furnace. After the protective gas temperature rose to 720℃, the furnace was opened and slag was skimmed off. Then, Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, and Mg-30wt.%Gd master alloy were added. After melting, the mixture was stirred for 2 minutes and held at that temperature for 10 minutes. The melt temperature was then raised to 750℃, the furnace was opened and slag was skimmed off, then pure Al was added and stirred for 3 minutes. After that, the temperature was held for 20 minutes to allow the pure Al to fully react with the other elements, obtaining a magnesium alloy melt.

[0046] casting: Set the pit-type resistance furnace to 720℃, insert a thermocouple into the molten magnesium alloy to accurately measure the temperature, and wait for the molten magnesium alloy to cool down to 720℃. First, remove the slag, then pour the molten magnesium alloy into a pure copper mold at 200℃. During casting, continuously purge the molten magnesium alloy with a protective gas mixture of CO2:SF6 = 99:1. After the molten magnesium alloy cools naturally, remove the magnesium alloy ingot from the mold and place it in water to continue cooling. After cooling to room temperature, remove it and let it air dry.

[0047] Solution heat treatment: The magnesium alloy ingot was placed in an alumina crucible, and then the ingot was completely covered with carbon powder to prevent it from contacting oxygen. The alumina crucible was then placed in a box-type resistance furnace for solution heat treatment at 510℃, with a heating rate of 5℃ / min and a holding time of 6 hours. After treatment, the magnesium alloy ingot was removed and rapidly cooled in 100℃ hot water. After complete cooling, it was removed and dried to obtain a T4 state magnesium alloy ingot.

[0048] Pulse current processing: The T4 state magnesium alloy ingot is machined into a long strip shape, the surface of the magnesium alloy ingot is polished, and then the long strip T4 state magnesium alloy ingot is clamped between two copper electrodes of the pulse current processing device, and the current density is set to 125A / mm. 2 The energizing time was controlled at 560ms to obtain the WE43 magnesium alloy material of this invention.

[0049] The WE43 magnesium alloy material prepared in Example 2, by mass percentage, consists of Y: 4.0%, Nd: 3.0%, Gd: 2.0%, Al: 2.0%, with the remainder being Mg. Its metallographic structure is as follows: Figure 2 and Figure 3 As shown, its SEM image is as follows: Figure 4 As shown.

[0050] Example 3 Pretreatment: Following the pretreatment method described above, cut 1000g of pure Mg, 215.5g of Mg-30wt.%Y master alloy, 172.5g of Mg-30wt.%Nd master alloy, 86.3g of Mg-30wt.%Gd master alloy, and 19.5g of pure Al. Use a grinder to remove the oxide scale and dirt from their surfaces. Place all materials in a 180℃ electric heating drying oven for later use. After cleaning the stainless steel crucible, alumina crucible, stirring rod, and slag ladle, prepare the refractory coating. The coating composition is talc:water:water glass = 3:2.5:2. After drying the crucible, stirring rod, and slag ladle, apply the coating and then bake them in a 180℃ drying oven for 20 minutes.

[0051] Melting: The temperature of the pit-type resistance furnace was set to 750℃, the protective gas composition was CO2:SF6 = 99:1, and the gas flow rate was 2L / min. A stainless steel crucible was placed in the pit-type resistance furnace and heated. When the stainless steel crucible reached 600℃, pure Mg was placed into the stainless steel crucible, and protective gas was simultaneously introduced into the furnace. After the protective gas temperature rose to 720℃, the furnace was opened to remove slag, and Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, and Mg-30wt.%Gd master alloy were added. After melting, the mixture was stirred for 3 minutes and held at that temperature for 10 minutes. The melt temperature was then raised to 780℃, the furnace was opened to remove slag, and then pure Al was added and stirred for 5 minutes, followed by holding at that temperature for 20 minutes to allow the pure Al to fully react with the other elements, obtaining a magnesium alloy melt.

[0052] casting: Set the pit-type resistance furnace to 720℃, insert a thermocouple into the molten magnesium alloy to accurately measure the temperature, and wait for the molten magnesium alloy to cool down to 720℃. First, remove the slag, then pour the molten magnesium alloy into a pure copper mold at 200℃. During casting, continuously purge the molten magnesium alloy with a protective gas mixture of CO2:SF6 = 99:1. After the molten magnesium alloy cools naturally, remove the magnesium alloy ingot from the mold and place it in water to continue cooling. After cooling to room temperature, remove it and let it air dry.

[0053] Solution heat treatment: The magnesium alloy ingot was placed in an alumina crucible, and then the ingot was completely covered with carbon powder to prevent it from contacting oxygen. The alumina crucible was then placed in a box-type resistance furnace for solution heat treatment at 530℃, with a heating rate of 5℃ / min and a holding time of 4 hours. After treatment, the magnesium alloy ingot was removed and rapidly cooled in 90℃ hot water. After complete cooling, it was removed and dried to obtain a T4 state magnesium alloy ingot.

[0054] Pulse current processing: The T4 state magnesium alloy ingot is machined into a long strip shape, the surface of the magnesium alloy ingot is polished, and then the long strip T4 state magnesium alloy ingot is clamped between two copper electrodes of the pulse current processing device, and the current density is set to 100A / mm. 2 The energizing time was controlled at 560ms to obtain the WE43 magnesium alloy material of this invention.

[0055] The WE43 magnesium alloy material prepared in Example 3 has the following composition by mass percentage: Y: 4.0%, Nd: 3.0%, Gd: 2.0%, Al: 1.5%, with the remainder being Mg.

[0056] Example 4 Pretreatment: Following the pretreatment method described above, cut 1000g of pure Mg, 215.5g of Mg-30wt.%Y master alloy, 172.5g of Mg-30wt.%Nd master alloy, 86.3g of Mg-30wt.%Gd master alloy, and 26g of pure Al. Use a grinder to remove the oxide scale and dirt from their surfaces. Place all materials in a 180℃ electric heating drying oven for later use. After cleaning the stainless steel crucible, alumina crucible, stirring rod, and slag ladle, prepare the refractory coating. The coating composition is talc:water:water glass = 3:2.5:2. After drying the crucible, stirring rod, and slag ladle, apply the coating and then bake them in a 180℃ drying oven for 20 minutes.

[0057] Melting: The temperature of the pit-type resistance furnace was set to 750℃, the protective gas composition was CO2:SF6 = 99:1, and the gas flow rate was 2L / min. A stainless steel crucible was placed in the pit-type resistance furnace and heated. When the stainless steel crucible reached 600℃, pure Mg was placed into the stainless steel crucible, and protective gas was simultaneously introduced into the furnace. After the protective gas temperature rose to 720℃, the furnace was opened to remove slag, and Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, and Mg-30wt.%Gd master alloy were added. After melting, the mixture was stirred for 3 minutes and held at that temperature for 10 minutes. The melt temperature was then raised to 780℃, the furnace was opened to remove slag, and then pure Al was added and stirred for 5 minutes, followed by holding at that temperature for 20 minutes to allow the pure Al to fully react with the other elements, obtaining a magnesium alloy melt.

[0058] casting: Set the pit-type resistance furnace to 720℃, insert a thermocouple into the molten magnesium alloy to accurately measure the temperature, and wait for the molten magnesium alloy to cool down to 720℃. First, remove the slag, then pour the molten magnesium alloy into a pure copper mold at 200℃. During casting, continuously purge the molten magnesium alloy with a protective gas mixture of CO2:SF6 = 99:1. After the molten magnesium alloy cools naturally, remove the magnesium alloy ingot from the mold and place it in water to continue cooling. After cooling to room temperature, remove it and let it air dry.

[0059] Solution heat treatment: The magnesium alloy ingot was placed in an alumina crucible, and then the ingot was completely covered with carbon powder to prevent it from contacting oxygen. The alumina crucible was then placed in a box-type resistance furnace for solution heat treatment at 530℃, with a heating rate of 5℃ / min and a holding time of 8 hours. After treatment, the magnesium alloy ingot was removed and rapidly cooled in 90℃ hot water. After complete cooling, it was removed and dried to obtain a T4 state magnesium alloy ingot.

[0060] Pulse current processing: The T4 state magnesium alloy ingot is machined into a long strip shape, the surface of the magnesium alloy ingot is polished, and then the long strip T4 state magnesium alloy ingot is clamped between two copper electrodes of the pulse current processing device, and the current density is set to 100A / mm. 2 The energizing time was controlled at 560ms to obtain the WE43 magnesium alloy material of this invention.

[0061] The WE43 magnesium alloy material prepared in Example 4 has the following composition by mass percentage: Y: 4.0%, Nd: 3.0%, Gd: 2.0%, Al: 2.0%, with the remainder being Mg.

[0062] Example 5 Unlike Example 2, 1000g of pure Mg, 184.7g of Mg-30wt.% Y master alloy, 144g of Mg-30wt.% Nd master alloy, 73.9g of Mg-30wt.% Gd master alloy, and 26g of pure Al were cut. The final WE43 magnesium alloy material, calculated by mass percentage, consisted of Y: 3.6%, Nd: 2.7%, Gd: 1.8%, Al: 2.0%, with the remainder being Mg.

[0063] Example 6 Unlike Example 2, 1000g of pure Mg, 254.3g of Mg-30wt.%Y master alloy, 198.3g of Mg-30wt.%Nd master alloy, 101.7g of Mg-30wt.%Gd master alloy, and 27.7g of pure Al were cut. The final WE43 magnesium alloy material, calculated by mass percentage, consisted of Y: 4.4%, Nd: 3.3%, Gd: 2.2%, Al: 2.0%, with the remainder being Mg.

[0064] Example 7 Unlike Example 2, the current density was set to 125 A / mm during electrical pulse processing. 2 The power-on time is controlled at 520ms.

[0065] Example 8 Unlike Example 2, the current density was set to 125 A / mm during electrical pulse processing. 2 The power-on time is controlled within 600ms.

[0066] Comparative Example 1 Unlike Example 2, pure Al was not added; instead, Zr was used, with 21.7 g of a Mg-30wt% Zr master alloy added. The final WE43 magnesium alloy material, by mass percentage, consisted of Y: 4.0%, Nd: 3.0%, Gd: 2.0%, Zr: 0.5%, with the remainder being Mg. The metallographic structure is as follows... Figure 5 As shown.

[0067] Comparative Example 2 Unlike Example 4, pure Al was not added; instead, Zr was used. The final WE43 magnesium alloy material, by mass percentage, consisted of Y: 4.0%, Nd: 3.0%, Gd: 2.0%, Zr: 0.5%, with the remainder being Mg.

[0068] Comparative Example 3 Unlike Example 2, electrical pulse processing is not used.

[0069] Solution heat treatment: The magnesium alloy ingot was placed in an alumina crucible, and then the ingot was completely covered with carbon powder to prevent contact with oxygen. The alumina crucible was then placed in a box-type resistance furnace for solution heat treatment at 525℃, with a heating rate of 5℃ / min and a holding time of 8 hours. The temperature of the box-type resistance furnace was then adjusted to 225℃ and held for 16 hours, followed by air cooling to room temperature. The metallographic structure of the prepared WE43 magnesium alloy material is shown below. Figure 6 As shown, the SEM image is as follows: Figure 7 As shown.

[0070] Comparative Example 4 Unlike Example 2, the solution heat treatment temperature was set to 550°C, the heating rate was 5°C / min, the holding time was 6h, and the rest of the operation remained the same.

[0071] Comparative Example 5 Unlike Example 2, the solution heat treatment temperature was set to 500°C, the heating rate was 5°C / min, the holding time was 6h, and the rest of the operation remained the same.

[0072] Comparative Example 6 Unlike Example 2, the current density was set to 80 A / mm during electrical pulse processing. 2 The power-on time is controlled within 500ms.

[0073] Comparative Example 7 Unlike Example 2, the current density was set to 150 A / mm during electrical pulse processing. 2 The power-on time is controlled at 650ms.

[0074] Test methods This invention tests the ultimate tensile strength, tensile yield strength, and elongation of various WE43 magnesium alloy materials prepared in the examples and comparative examples. Ultimate tensile strength is abbreviated as UTS, tensile yield strength as TYS, and elongation as EL. The test methods are as follows: The tensile properties of the alloy were tested using a WH-5000 microcomputer-controlled electronic universal testing machine at a tensile rate of 0.5 mm / min. Tensile specimens were prepared according to GB6397-86, and their dimensional structure is shown in the figure below. Figure 9 As shown, the dimensions are in millimeters.

[0075] After clamping the tensile specimen onto one end of the force sensor, the equipment is zeroed, and then the other end is clamped to eliminate experimental error caused by preload during clamping. After the experiment, tensile-displacement data can be obtained from the equipment's software. This data is imported into Origin software, and the stress-strain diagram is calculated using the cross-sectional dimensions measured before tensioning and the actual tensile length. The ultimate tensile strength and elongation can then be obtained. Using the specified plastic elongation strength Rp0.2 as a measure of yield strength, the stress corresponding to 0.2% plastic strain on the stress-strain diagram is the tensile yield strength.

[0076] The test results of ultimate tensile strength, tensile yield strength, and elongation of Embodiments 1-8 and Comparative Examples 1-7 of the present invention are shown in Table 1: Table 1. Properties of WE43 Magnesium Alloy As can be seen from the data in Table 1, the WE43 magnesium alloy materials prepared in Examples 1 to 8 of the present invention can effectively balance tensile strength and elongation.

[0077] Comparing Comparative Examples 1 and 2 with the corresponding embodiments, it can be seen that if Zr is replaced with Al, the tensile strength of the final magnesium alloy material can be guaranteed, but the elongation is nearly doubled, far inferior to the WE43 magnesium alloy material prepared in the corresponding embodiments. After Al replaces Zr, the tensile yield strength and tensile strength of the alloy not only do not decrease, but also slightly increase, with the tensile yield strength increasing by 7% to 10%, the ultimate tensile strength increasing by 2% to 4%, and the elongation increasing by as much as 92% to 146%. This fully demonstrates the technical feasibility of Al as a modifier—Al segregates at grain boundaries to reduce grain boundary energy and inhibit grain growth, while reacting with Y / Nd / Gd to generate thermally stable phases such as Al2RE, which act as heterogeneous nucleation cores, achieving a synergistic effect of grain refinement strengthening and second-phase strengthening, and the plasticity is far superior to the traditional Zr refinement system.

[0078] The comparison results between Comparative Example 3 and Example 2 show that the alloy obtained by EPT treatment has higher yield strength and tensile strength. Specifically, the yield strength is increased by 24.4%, while the tensile strength is increased by 11.7%. This result is due to the recrystallization and grain refinement induced by EPT treatment, which increases the dislocation density. The combined effect of grain refinement strengthening and dislocation strengthening is superior to that of Mg precipitated by traditional aging. 19 Al 12 Phase strengthening was achieved, and the elongation rate increased by 98.4%, nearly doubling. This is because EPT treatment promotes the dissolution, spheroidization, and uniform distribution of the second phase, reducing the cutting effect of coarse precipitates on the matrix. In terms of efficiency, the EPT treatment time is only 560 ms, less than 1 second, while traditional aging requires more than 16 hours, resulting in an efficiency improvement of approximately 100,000 times, demonstrating significant industrial value. Further based on... Figures 2-4 and Figures 6-7 The comparison shows that the WE43 magnesium alloy material prepared in Example 2 has a smaller grain size. This indicates that electrical pulse treatment can promote the precipitation of the second phase while refining the grains, thereby effectively reducing the grain size and increasing the dislocation density to improve the alloy strength. In contrast, aging heat treatment causes grain growth while precipitating the second phase, and through the precipitation of Mg... 19 Al 12 The aging precipitation of the phase strengthens the alloy. Comparison results between Comparative Example 4 and Example 2, and... Figure 1 It can be seen that the excessively high solution heat treatment temperature in Comparative Example 4 led to grain boundary migration and grain growth. Compared to Example 2, the ultimate tensile strength and tensile yield strength decreased slightly, with the tensile yield strength decreasing by 19.2%, but the elongation decreased significantly by 33.6%. Conversely, excessively low temperatures, as shown in the data from Comparative Example 5, can lead to conditions such as Mg... 24 Y5, Mg 41The eutectic phases such as Nd5 do not dissolve sufficiently, resulting in insufficient rare earth element concentrations in the solid solution. Electro-pulse treatment mainly accelerates solute diffusion and promotes the nucleation of precipitated phases. If the temperature is below the threshold required for eutectic phase dissolution, such as 510℃~525℃ for WE43 magnesium alloy, Mg... 24 The high residual content of stable phases such as Y5 and the inherently insufficient supersaturation of the solid solution affect the subsequent electro-pulse effect. Within the threshold temperature range, it is crucial to ensure sufficient dissolution of the eutectic phase while avoiding excessive grain coarsening, thus providing the optimal matrix state for subsequent electro-pulse treatment. According to the data from Comparative Examples 6 and 7 and Example 2, the elongation of the WE43 magnesium alloy gradually increases with increasing energizing time, but the tensile strength initially increases and then decreases. This is because with increasing energizing time, the dislocation density gradually increases, and solid solution strengthening, grain refinement strengthening, and dislocation strengthening collectively improve the alloy's tensile strength. However, as the energizing time increases, the number of subgrains also increases. When the energizing time exceeds 600 ms, the strength loss due to the increased dislocation density outweighs the improvement from solid solution strengthening and grain refinement strengthening, resulting in a decrease in the alloy's tensile strength but a continued increase in elongation. Within the range of 100 A / mm² to 125 A / mm² and 520 ms to 600 ms, the WE43 magnesium alloy material achieves the best balance between grain refinement strengthening, dislocation strengthening, and thermal effects, resulting in optimal synergy between strength and plasticity. In summary, this invention offers the following beneficial effects:

[0079] 1. Al replaces Zr for precise composition control. Al has a melting point of only 660℃ and can be added directly in pure form without intermediate alloys, avoiding uneven distribution caused by density differences. Al has a high solid solubility in magnesium matrix, approximately 12.7wt%, which is much higher than that of Zr. It is less prone to sedimentation and oxidation, and its burn-off rate is much lower than that of Zr, allowing for more precise composition control. At the same time, after replacing Zr with Al, the alloy strength does not decrease but increases, with tensile yield strength increasing by 7%~10% and elongation increasing by nearly 1.5 times.

[0080] 2. The casting time window limitation is eliminated. After adding Al, there is no strict casting time requirement, unlike Zr which must be cast within 30 minutes. The process flow design is more flexible. The electrical pulse treatment reduces the post-processing time from tens of hours of traditional aging to hundreds of milliseconds, which is a revolutionary improvement in process efficiency. 3. Significantly reduces raw material costs. The price of pure Al is only a fraction of the price of Zr of the same quality, resulting in a substantial reduction in raw material costs. The elimination of the need for expensive Mg-Zr master alloys further reduces procurement and storage costs. The process is simplified by eliminating strict time windows and replacing long-term aging with electrical pulses, thereby reducing equipment and energy costs. 4. Synergistic improvement of strength and plasticity: The process of combining Gd alloying, Al modification, solution heat treatment and electric pulse treatment results in the final properties of WE43 magnesium alloy: ultimate tensile strength ≥309MPa, yield strength ≥219MPa, elongation ≥10.6%, achieving a balance between high strength and high plasticity, which is superior to the traditional Zr refinement and aging heat treatment process.

[0081] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described in this invention to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art, once they understand the inventive concept of this invention, can make other changes and modifications to these embodiments, and all such changes and modifications fall within the scope of this invention.

[0082] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. If such modifications and variations fall within the scope of equivalents of this invention, then this invention also intends to include these modifications and variations.

Claims

1. A WE43 magnesium alloy material, characterized in that, The composition, by mass percentage, includes at least the following components: Y: 3.6%~4.4%, Nd: 2.7%~3.3%, Gd: 1.8%~2.2%, and Al: 1.5%~2.0%, with the balance being Mg.

2. A method for preparing the WE43 magnesium alloy material according to claim 1, characterized in that, Includes the following steps: The pretreated raw materials were melted to obtain magnesium alloy melt; Magnesium alloy melt is cast to obtain magnesium alloy ingots; Magnesium alloy ingots were subjected to solution heat treatment to obtain magnesium alloy ingots in the T4 state. The WE43 magnesium alloy material was obtained by subjecting a T4 state magnesium alloy ingot to electrical pulse treatment. The raw materials include pure Mg, Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, Mg-30wt.%Gd master alloy, and pure Al.

3. The method for preparing the WE43 magnesium alloy material according to claim 2, characterized in that, The raw materials, by mass percentage, consist of the following components: Mg-30wt.% Y master alloy 15%~18.3%, Mg-30wt.% Nd master alloy 11.3%~14.3%, Mg-30wt.% Gd master alloy 7.5%~9.2%, and Al 1.5%~2.0%, with the balance being pure Mg.

4. The method for preparing the WE43 magnesium alloy material according to claim 2, characterized in that, The pretreatment method includes drying the raw materials and preheating them to 180°C~200°C.

5. The preparation method according to claim 2, characterized in that, The melting step includes: Pure Mg is heated to 720℃~750℃ to melt and held at that temperature to obtain the first melt; Mg-30wt.%Y master alloy, Mg-30wt.%Nd master alloy, and Mg-30wt.%Gd master alloy were added to the first melt, mixed evenly, and kept at a certain temperature to obtain the second melt. After heating the second melt to 750℃~780℃, add pure Al, mix evenly and keep warm to obtain the third melt; After cooling the third melt to 690℃~710℃, a magnesium alloy melt is obtained.

6. The method for preparing the WE43 magnesium alloy material according to claim 2, characterized in that, Both melting and casting are carried out in a protective gas, which is a mixture of CO2 and SF6 in a volume ratio of 99:

1.

7. The method for preparing the WE43 magnesium alloy material according to claim 2, characterized in that, The casting process also includes the step of immersing the solidified magnesium alloy melt in water for cooling.

8. The preparation method according to claim 2, characterized in that, The solution heat treatment includes wrapping the Mg alloy ingot with carbon powder and holding it at a temperature of 510℃~530℃ and a heating rate of 5℃ / min for 4h~8h. And / or, the solution heat treatment further includes a cooling step, wherein the cooling temperature is 90℃~100℃.

9. The preparation method according to claim 2, characterized in that, Before undergoing electrical pulse treatment, the T4 state Mg alloy ingot is machined into a long strip and its surface is polished.

10. The preparation method according to claim 2, characterized in that, The current density of the electrical pulse processing is 100 A / mm. 2 ~125A / mm 2 The power-on time is 520ms~600ms.